Morphological characteristic of intracerebral hemorrhage in rats and correlation of its volume with results of behavioral tests - Zolotko, Kyrylo M.; Sukach, Oleksandr M.; Kompaniiets, Antonina M.; Liubomudrova, Kateryna S. (Ukrainian Neurosurgical Journal, 2021)
The intracerebral hemorrhage is associated with severe complications and high mortality. Currently there are no effective methods of treatment of this disease while the standard collagenase model of intracerebral hemorrhage is not described sufficiently. Objective. To analyze morphological characteristics of the collagenase model of intracerebral hemorrhage, and develop the regression formula predicting the hemorrhage volume based on the results of behavioral tests. Materials and methods. The experiments were carried out on 7 white male rats weighing 250-400 g aged 11-13 months. All animals underwent surgery to simulate intracerebral hemorrhage. Rats were anesthetized and then, stereotactically, using a needle with a diameter of 0.47 mm, 0.2 units of collagenase type IV were slowly injected into the left striatum. The day after the intracerebral hemorrhage, functional disabilities developed in rats were studied using beam walking test, neurological score test and adhesive removal test. Immediately after performing behavioral tests, the rats were sacrificed by decapitation. After the brain formalin fixation, serial sections on a vibromicrotome of 200 µm thick each in the anteroposterior direction with following morphological examination were made. Results. It was revealed that the collagenase model of intracerebral hemorrhage is associated with a large variability of the hemorrhage volume. It also had an irregular rugged shape and marks of repeated diapedetic hemorrhages of about 0.6 mm depth. The center of intracerebral hemorrhage along the anteroposterior axis was in average 0.5 mm posterior of the actual site of collagenase injection. The combined use of the neurological score test, the beam walking test and the adhesive removal test in the collagenase model can help estimate the probable intracerebral hemorrhage volume on the 1st day using the regression formula. Conclusions. Technical details identified in our study can help researchers in planning and conduction of correct experiments related to intracerebral hemorrhage.